Exploring resilience among hospital workers: a Bayesian approach - Uccella, Laura; Mascherona, Ilenia; Semini, Sebastiano; Uccella, Sara (Frontiers in Public Health, 2024)
Background and importance: Healthcare professionals face significant workloads, as their roles are among the most demanding and stressful. Resilience serves as a crucial factor in helping them cope with the challenges encountered in their work environment and effectively manage stress. Assessing the level of resilience among healthcare workers and identifying potential variations across different groups is essential for effective public health management, preventing burnout, and ultimately enhancing patient care. Objective: To assess the resilience of various categories of workers operating within a tertiary care multisite hospital and understanding if there are any differences in resilience, based on their characteristics, the type of department they work in, and personality traits. Design, setting and participants: This was a cross-sectional study conducted in January 2024 at EOC, a multi-site tertiary care hospital located in Southern Switzerland. 1197 hospital workers answered an online survey which included: 1) an ad hoc questionnaire on personal/job characteristics, well-being-related activities, satisfaction level regarding communication, collaboration, support, and training opportunities in the workplace, 2) the Connor-Davidson Resilience Scale 10-Item on resilience, and 3) the Big Five Personality Inventory 10-item on personality traits. Outcome measures and analysis: Proportion of resilient and highly resilient individuals within the various categories of workers were analysed with bayesian approach and Bayesian robust regression. Main Results: Being part of the hospitality staff, working as a doctor, and having a male sex were associated to the highest scores of resilience. Surgery and emergency departments had the highest proportion of highly resilient individuals. Male sex, older age, seniority, higher hierarchical rank, engagement in physical activities, relaxation or mindfulness practices, religiosity, perception of good collaboration, communication, support, and physical activity correlated with higher resilience skills.This cross-sectional study found that physicians and hospitality staff within our multisite Swiss hospital are more resilient compared to other categories of hospital workers, and among departments, those working in surgery and Emergency Medicine. Enhancing our comprehension of resilience is crucial for more precise management of healthcare systems and the development of employment policies aimed at sustaining the capacity of healthcare systems to serve patients effectively, while also mitigating shortages of healthcare professionals.